Knowledge regarding breast self-examination among the women in Nepal: A meta-analysis - Sathian, Brijesh; Asim, Mohammad; Mekkodathil, Ahammed; James, Sruthi; Mancha, Angela; Ghosh, Arnab (Nepal Journal of Epidemiology, 2019)
Background: Screening interventions for the early diagnosis of breast cancer are associated with better clinical outcomes. Developing nations such as Nepal reportedly have lesser frequency of female university graduates (UGs) and therefore public awareness and education remains central in the early diagnosis. The current meta-analysis was aimed to assess the knowledge about breast self-examination (BSE) among women of Nepal. Materials and Methods: We have conducted the literature search using electronic databases such as PubMed, MEDLINE, Cochrane library and Google scholar. The search terms utilized were “breast self-examination”; “knowledge”, “awareness”; and “attitude” in various combinations AND “Nepal” in the title or abstract. Additional searches were conducted with the help of cross references quoted in the selected studies and review articles. Data were retrieved using excel sheets which were pilot tested. Data were independently abstracted by the four authors using a standardized data collection form. Findings from the various studies were pooled together for the sake of analysis, if appropriate. Results: The search yielded 36 articles; 27 duplicates and review articles were excluded and a further 4 articles not relevant were excluded. Finally, 5 original studies met the inclusion criteria. Total pooled sample size for assessing knowledge was 1910. The overall pooled knowledge about breast self-examination was found to be 27% with a 95% CI [26-31]. Conclusion: The pooled estimates demonstrated that the overall knowledge of breast self-examination was inadequate among women in Nepal. Therefore, prompt capacity building measures are warranted to enhance the public awareness towards BSE.